AB0132 Fraxinellone attenuates rheumatoid inflammation in mice. (12th June 2018) - Jung, S.M.; Lee, J.; Baek, S.Y.; Lee, J.; Jang, S.G.; Hong, S.-M.; Kim, D.; Kim, H.W.; Kwok, S.-K.
Abstract : Background: Fraxinellone is isolated from Dictamnus dasycarpus, a traditional herbal medicine that attenuates inflammatory conditions. 1, 2 Recent studies have suggested that fraxinellone has a potential therapeutic effect in animal models with inflammatory diseases. 3–5 Objectives: We aimed to evaluate the therapeutic effect of fraxinellone on inflammatory arthritis and identify the underlying mechanisms. Methods: Fraxinellone (7.5 mg/kg) or a vehicle control was injected into mice with collagen-induced arthritis (CIA). The severity of arthritis was evaluated clinically and histologically. The differentiation of CD4 +T cells and CD19 +B cells was investigated in the presence of fraxinellone. Osteoclastogenesis after fraxinellone treatment was evaluated by staining with tartrate-resistant acid phosphatase (TRAP) and by measuring the mRNA levels of osteoclastogenesis-related genes. Results: Fraxinellone attenuated the clinical and histologic features of inflammatory arthritis in CIA mice. Fraxinellone suppressed the expression of interleukin-17, and T helper 17 cell-related transcription factors (RORγt and phosphorylated STAT3) in CD4 +T cells. CD19 +B cells showed lower expression of activation-induced cytidine deaminase (AID) and Blimp-1 after treatment with fraxinellone. The formation of TRAP-positive cells and the expression of osteoclastogenesis-related markers were reduced in the presence of fraxinellone. Inhibition of interleukin-17 and osteoclastogenesis was also observed in experiments using human peripheral mononuclear cells. Conclusions: Fraxinellone alleviated synovial inflammation and osteoclastogenesis in mice. The therapeutic effect of fraxinellone was associated with the inhibition of cellular differentiation and activation. The data suggests that fraxinellone could be a novel treatment for inflammatory arthritis, including rheumatoid arthritis. References: [1] Jiang Y, Li SP, Chang HT, Wang YT, Tu PF. Pressurized liquid extraction followed by high-performance liquid chromatography for determination of seven active compounds in Cortex Dictamni. Journal of chromatography A2006;1108:268–272. [2] Sun J, Wang X, Wang P, Li L, Qu W, Liang J. Antimicrobial, antioxidant and cytotoxic properties of essential oil from Dictamnus angustifolius. Journal of ethnopharmacology2015;159:296–300. [3] Wu XF, Ouyang ZJ, Feng LL, Chen G, Guo WJ, Shen Y, Wu XD, Sun Y, Xu Q. Suppression of NF-kappaB signaling and NLRP3 inflammasome activation in macrophages is responsible for the amelioration of experimental murine colitis by the natural compound fraxinellone. Toxicology and applied pharmacology2014;281:146–156. [4] Sun Y, Qin Y, Gong FY, Wu XF, Hua ZC, Chen T, Xu Q. Selective triggering of apoptosis of concanavalin A-activated T cells by fraxinellone for the treatment of T-cell-dependent hepatitis in mice. Biochemical pharmacology2009;77:1717–1724. [5] Jiang S, Nakano Y, Rahman MA, Yatsuzuka R, Kamei C. Effects of a Dictamnus dasycarpus T. extract on allergic models in mice. Bioscience, biotechnology, and biochemistry2008;72:660–665. Acknowledgements: This research was supported by the Catholic Medical Centre Research Foundation made in the program year of 2014. Disclosure of Interest: None declared